Antioxidant activity and stability of pigments extracted from selected plants as potential colourant - Goh, Su May (2014)
Natural colourants in cosmetics product development is increasing due to the public awareness on the adverse health effect. This study was carried out to determine antioxidant activity and colour stability of red dragon fruit (Hylocereus polyrhizus), butterfly pea flower (Clitoria tematea) and pandan leaves (Pandanus amaryllifolius). The antioxidant activity was determined in dfferent concentration of methanol extract by 2,2- diphenylpicrylhydrazyl (DPPH) assay to evaluate the properties of plant samples for scavenging free radicals and ascorbic acid as a standard antioxidant. The concentration of stock solution for each sample, DPPH and ascorbic acid extract were prepared at 10, 5, 2.5, 1.25, 0.625mg/ml. From the analysis, the maximum percentage of scavenging activity of Hylocereus polyrhizus, Clitoria ternatea and Pandanus amaryllifolius were 72.05%, 76.59% and 68.45% respectively while for standard ascorbic acid were 97.26% at 10mg/m1 concentration. Based on the results, it shows that the scavenging activity was increase with the increase of concentration of methanol extract. From ANOVA analysis, DPPH free radical scavenging effect of the extract was compared with ascorbic acid and it show significantly different result (P<0.05). Furthermore, this study also aimed at determining the colour stability of the three samples based on the storage days, light treatment and heat treatment. The solution of colour was heated at 30°C, 50°C, 70°C and 90°C respectively while for the light treatment, solutions were stored in light and dark area. The samples obtained was analyzed and tested by using a spectrophotometer, giving results of the changes of colour. Based on the results, low temperature and shaded area are the best in maintaining the colour stability. Thus, the colour stability of these samples based on data collected is suitable to be a natural colourant with a high stability to replace synthetic colourant and support that these water extracts have potential antioxidant activity.